Peran Mediasi Kinerja Keuangan dalam Hubungan antara Struktur Modal dengan Nilai Perusahaan - Umu Khouroh; Sari Wenni Nurindah; Maya Mega Puspita (University of Merdeka Malang, 2022)
This study aims to examine the impact of capital structure and financial performance on firm value and the mediating role of financial performance in the relationship between capital structure and firm value. The population in this study is a manufacturing company in the consumer goods sector. The sample in this study was 8 manufacturing companies in the consumer goods sector purposive sampling with the largest assets. Data obtained from financial reports that have been published. The analysis technique uses a path analysis model. The results of this study provide evidence that capital structure and financial performance have a major impact on increasing firm value, as well as capital structure which has a major impact on financial performance.